A proposal of material modeling for swimwear considering anisotropy and viscosity - Nagaoka, T.; Matsuda, A.; Shimana, T.; Omori, K. (Procedia Engineering, 2012)
This paper investigates an engineering approach using numerical analysis on a new constitutive model of the competitive swimwear. First, an anisotropic hyperelastic model was proposed. It reproduces the mechanical characteristics and its material modulus are estimated by the biaxial loading test. From this biaxial loading test, the fabrics for competitive swimwear have shown nonlinear elasticity which is regarded as hyperelasticity like rubber. In addition, they also have shown anisotropic characteristic which is dependent on the directions of warp and weft yarn. An anisotropic model is represented by the power series of invariants of stretch and shear deformation in each yarn. In order to verify the reproducibility, the material parameters of the proposed model were determined by nonlinear least squares approximation and the theoretical value was introduced. Second, from the cyclic loading test results, the materials have shown the viscosity and stress-softening effect. We proposed softening model for cyclic deformation.